The Association between Children’s Behavior and Parenting of Caregivers: A Longitudinal Study in Japan - Suzuki, Kota; Kita, Yosuke; Kaga, Makiko; Takehara, Kenji; Misago, Chizuru; Inagaki, Masumi (Frontiers in Public Health, 2016)
The purpose of this study was to elucidate the association between children’s behavior (i.e., prosocial and problematic behavior) and the parenting style (i.e., laxness and overreactivity) of their caregivers by using longitudinal data in the Japanese population. This data was collected when the children were 7.5 and 9 years. We proposed three hypotheses: children’s behavior at 7.5 years will predict their behavior at 9 years; children’s behavior at 7.5 years will predict the parenting of their caregivers; and the parenting style of caregivers will affect their children’s behavior at 9 years. We evaluated children’s behavior and parenting behavior using a strength and difficulties questionnaire and a parenting scale. The hypotheses were tested using structural equation modeling (SEM). The results of the SEM showed that children’s behavior at 7.5 years predicted their behavior at 9 years. Children’s problematic behavior at 7.5 years triggered overreactive parenting in their caregivers at 9 years, which increased problematic behavior and decreased prosocial behavior in the children at 9 years. These findings indicate the association between children’s behavior and the parenting style of caregivers in Japan.